Membangun wirausaha retail berbasis kebutuhan lokal - Pratama, Ikhwan; Willy, Firdi; Wicaksana, Yosua (Lentera Jurnal Pengabdian Masyarakat, 2025)
Developing retail entrepreneurship based on local needs is a strategic effort to increase community economic resilience while addressing the specific needs of consumers in the local area. This project aims to design and implement a retail entrepreneurship model that aligns with the consumption patterns, cultural characteristics, and socio-economic conditions of the Cikarang community. Through the application of Community-Based Participatory Action Research (CBPAR) methods combined with Design Thinking, this project actively involves local businesses and communities in the design, testing, and evaluation of relevant and sustainable retail business models. The methodology used includes in-depth interviews, market observations, consumer surveys, and the creation of retail product and service prototypes based on community input. Initial results indicate increased product relevance, consumer satisfaction, and the potential for community economic empowerment. Furthermore, this approach fosters the strengthening of local identity and increases the competitiveness of retail businesses at the community level. These findings demonstrate that the integration of participatory methods and design thinking can significantly improve the adaptability and sustainability of locally-based retail entrepreneurship and has the potential for replication in other regions. Keywords: Retail entrepreneurship, local needs, CBPAR, design thinking, community empowerment, sustainability.